P338 Transmural healing is not associated with less disability than complete endoscopic mucosal healing: a prospective study in a patient with Crohn's disease. (30th January 2023) - Yzet, C; Brazier, F; Hautefeuille, V; Grados, L; Decrombecque, C; Diouf, M; Fumery, M
Abstract: Background: Crohn's disease (CD) is associated with disability by affecting physical and emotional well-being, and by altering social interactions. In the era of treat to target, endoscopic remission has become the therapeutic target to prevent parietal destruction and disability. A deeper remission such as transmural healing would reduce long-term complications related to CD. The impact of transmural healing on disability is currently unknown. Methods: We conducted a monocentric cross-sectional study between September 2019 and January 2022. Patients followed for CD in endoscopic remission (CDEIS <4) who underwent within < 4 weeks an intestinal ultrasound (IUS) and a disability assessment by an IBD-disk were consecutively included. Four groups were considered: (A) transmural healing defined by the combination of complete endoscopic healing (CDEIS=0) and ultrasound healing (bowel wall thickness (BWT) less than 3 mm), (B) complete endoscopic healing, (C) ultrasound healing and (D) no healing. Moderate to severe disability was defined as an overall score ≥ 40. Results: A total of 85 patients were included. Forty-four (51.7%) were female, the median age and disease duration were respectively 38 years (interquartile range [IQR], 33-44) and 12.0 years (IQR, 5-20). There was no difference between the four groups in terms of age, sex, BMI, smoking status, disease location or phenotype or number of biologics failure. The median global IBD-Disk score was 25 (IQR, 9-41) and 24 patients (28.2%) had moderate to severe disability. Transmural healing (group A) was observed in 40 patients (47.1%). Moderate to severe disability was identified in 17.5% (7/40) of patients with transmural healing, 25% (4/16) with endoscopic healing, 44.4% (8/18) with ultrasound healing and 45.4 % (5/11) without healing. In univariate analysis, transmural healing reduced the risk of severe disability (group C vs A OR = 3.77, 95% CI [1.10, 13.45], p = 0.035), group D vs A OR = 3 .75, 95% CI [0.91, 17.12], p=0.063). There was no difference in terms of severe disability between patients with transmural healing and complete endoscopic healing (group B versus A OR = 1.57 95% CI [0.36, 6.23], p = 0.525). Conclusion: Transmural healing did not provide any benefit in terms of disability compared to complete endoscopic healing. Mucosal healing therefore remains the objective to be achieved in order to reduce the risk of short-term disability.